2012
DOI: 10.1002/ibd.21940
|View full text |Cite
|
Sign up to set email alerts
|

Long-term MRI-guided combined anti-TNF-α and thiopurine therapy for crohnʼs perianal fistulas

Abstract: Combination anti-TNF and thiopurine therapy provides sustained benefit in patients with perianal CD fistula. Early clinical response is associated with subsequent clinical remission. Radiological healing is slower than clinical healing. Radiologically healed fistula tracts maintain healing on infliximab but can recur after cessation of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
4
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 26 publications
7
105
4
7
Order By: Relevance
“…8,12 However, there has been no objective method for quantification of fistula volume and this has therefore not been included in MRI scoring systems to date. 8,12,17,19 Studies of surgical treatment have also struggled to identify a robust, objective measure of radiological improvement. 20 The present study has shown that volume of perianal fistula in patients with CD can be reliably measured by MRI with very good inter-and intra-observer agreement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,12 However, there has been no objective method for quantification of fistula volume and this has therefore not been included in MRI scoring systems to date. 8,12,17,19 Studies of surgical treatment have also struggled to identify a robust, objective measure of radiological improvement. 20 The present study has shown that volume of perianal fistula in patients with CD can be reliably measured by MRI with very good inter-and intra-observer agreement.…”
Section: Discussionmentioning
confidence: 99%
“…10 CD is a chronic relapsing and remitting disease as are its fistulising complications, 11 so clinical remission cannot be determined at individual time points, as the very nature of discharge is sporadic. Furthermore, closure of an external opening does not necessarily equate to deep healing of the tracts, 12 or indeed improved quality of life. 8 Pelvic MRI has been shown to be the most accurate method for classification of the primary tract and secondary extensions; 13 the recognition and treatment of the latter being essential to ensure satisfactory healing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The aim of this study was to review long-term outcomes of patients treated with biological therapy for perianal Crohn's fistula at our institution. Methods: A local database of patients treated at our tertiary institution from 2005 to 2016 was established for patients on biologic (anti-TNF) therapy.…”
Section: P509mentioning
confidence: 99%
“…En pacientes con EC y compromiso inflamatorio se consideró remisión endoscópica de la mucosa a un puntaje ≤ 2, según el score endoscópico SES-CD 21,22 . En pacientes con EC y compromiso perianal se consideró una buena respuesta radiológica la reducción de la fístula a lo menos en 50% en el control por RM de pelvis 23 .…”
Section: Materials Y Métodounclassified